Coexistence of Charcot–Marie–Tooth disease type 1A and chronic inflammatory demyelinating polyradiculoneuropathy with conduction blocks. Issue 5 (22nd June 2016) - Shimizu, Kazutaka; Hanajima, Ritsuko; Shimizu, Takahiro; Usui, Ryo; Yanagida, Atsuko; Akutsu, Tsugio; Iizuka, Takahiro; Nishiyama, Kazutoshi
Abstract: We present a 47‐year‐old woman with upper extremity muscle weakness and sensory disturbance during a slowly progressive course of leg muscle weakness. First, she was diagnosed with chronic inflammatory demyelinating polyradiculoneuropathy. However, with gene analysis of PMP22 duplication, she was diagnosed with Charcot–Marie–Tooth type 1A. In the electrophysiological study, nerve conduction blocks were shown, which is inconsistent with Charcot–Marie–Tooth type 1A. Intravenous immunoglobulin therapy improved both her symptoms and the conduction blocks. We suggest that inflammatory demyelinating polyradiculoneuropathy was associated with Charcot–Marie–Tooth type 1A in this patient. The presence of the conduction blocks could be a hallmark of the associating inflammatory demyelinating polyradiculoneuropathy. Intravenous immunoglobulin therapy might be partly effective in such patients.